A novel era of probiotics in dentistry. A double-blind randomised clinical trial - Ruhee Chawla; Aarti Patil; Vibhuti Dilip Mistry; Alka Sanjay Waghmare; Sunil Ronad; Chetan Vinay Deshmukh (Journal of Indian Association of Public Health Dentistry, 2024)
Introduction: The use of chemical agents has dramatically increased and holds a great promise for the prevention of dental plaque, of which chlorhexidine is considered the gold standard. New novel probiotic mouthrinses are being developed to combat the adverse effects of chlorhexidine mouthrinse. Objective: The objective of this study was to compare the effectiveness of probiotic mouthrinse with chlorhexidine mouthrinse for the treatment of chronic periodontitis as an adjunct to scaling and root planing. Materials and Methods: The patients were randomly divided into two groups of 7 subjects each. Group A (Control) and Group B (Test) had scaling and root planing along with chlorhexidine mouthrinse and probiotic mouthrinse, respectively. Clinical parameters measured at baseline and 45 days were gingival index, plaque index, probing pocket depth, and clinical attachment loss. Microbial analysis was done by collecting plaque samples at baseline and 45 days. Paired t-test was used for intragroup and intergroup comparisons, whereas independent t-test was used for intergroup comparisons. Keeping the level of significance at 5%, the significant difference was adjusted at P ≤ 0.05. Results: The mean clinical parameters were significantly reduced for both treatment groups posttherapy. The microbiological data analysis (colony-forming units/ml) showed that after the therapy, there was a significant reduction in both the groups with Group B > Group A. Conclusion: Probiotics can in the near future and with more research serve to be as natural candidates to substitute antibiotics and their derivatives.